A taxonomic revision of the genus Digitaria (Panicoideae: Poaceae) in mainland Southeast Asia - Boonsuk, Boonchuang; Chantaranothai, Pranom; Hodkinson, Trevor R. (Phytotaxa, 2016)
A taxonomic revision of the genus Digitaria (Poaceae) is presented for mainland Southeast Asia (Cambodia, Lao PDR, Myanmar, Peninsular Malaysia, Thailand and Vietnam). A total of 27 species (29 taxa) is enumerated. Two cultivated species, D. eriantha and D. milanjiana, are excluded from this account. A key to sections and species is provided and subgenus Leptoloma is reduced to sectional rank. Taxon descriptions include distribution and ecological data, conservation status, and notes on each species. Digitaria effusa and D. hentyi are reduced to synonyms of D. abyssinica, and D. siamensis is a synonym of D. sparsifructus. The lectotype is designated for D. stricta var. glabrescens.